Analysis of Occupational Safety and Health at Oil Plus Filling Station Installations: Literature Review - Fanny Dimasruhin Fanny; Doni Hikmat Ramdhan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Public Fuel Filling Station Installation which is an installation for distributing fuel oil into motor vehicle fuel tanks, with a significant risk of danger. The number of work accidents that occur at fuel filling stations continues to increase from 2018-2020. Program Safety and health need to be pursued to protect workers from the possibility of accidents and work-related diseases. Objective: This research aims to determine potential dangers and prevent accidents and occupational diseases among fuel station workers. Method: This research uses the